A Comparison of Human and Computational Melody Prediction Through Familiarity and Expertise - Pesek, Matevž; Medvešek, Špela; Podlesek, Anja; Tkalčič, Marko; Marolt, Matija (Frontiers in Psychology, 2020)
Melody prediction is an important aspect of music listening. The success of prediction, i.e. whether the next note played in a song is the same as the one predicted by the listener, depends on various factors. In the paper, we present two studies, where we assess how music familiarity and music expertise influence melody prediction in human listeners, and, expressed in appropriate data/algorithmic ways, computational models. To gather data on human listeners, we designed a melody prediction user study, where familiarity was controlled by two different music collections, while expertise was assessed by adapting the Music Sophistication Index instrument to Slovenian language. In the second study, we evaluated the melody prediction accuracy of computational melody prediction models. We evaluated two models, the SymCHM and the Implication-Realization model, which differ substantially in how they approach melody prediction. Our results show that both music familiarity and expertise affect the prediction accuracy of human listeners, as well as of computational models.